Pemeriksaan kesehatan dan komunikasi, informasi dan edukasi pada masyarakat di Galesong Utara, Kabupaten Takalar - Ira Widya Sari; Desi Reski Fajar (INDRA: Jurnal Pengabdian kepada Masyarakat, 2021)
In the context of strengthening health development that prioritizes promotive-preventive efforts, without overruling curative-rehabilitative efforts by involving all components of the nation in promoting a healthy paradigm. IEC reduces disease expenditure, avoids a decrease in population expenditure, and decreases health care costs due to disease expenditure and health expenditure. This IEC activity is an effort to improve public health in North Galesong District, Takalar Regency, went well and was enthusiastically welcomed by the community, the purpose of this activity was to increase public knowledge about health information relating to the illness suffered. The dedication activity was attended by 45 participants, from the community service activities, it can be concluded that the community has begun to understand and comprehend and further increase knowledge about health information concerning the illness suffered. And the community is able to control health well in order to achieve improved health.